The Impact of COVID-19 on Pediatric Dentistry: A Study of the Knowledge and Attitudes of Parents in Jordan - Al-Ajlouni, Lana; Abu-Ghazaleh, Suha; Rajab, Lamis (Jordan Medical Journal, 2023)
Aims: This study aimed to assess parental knowledge of COVID-19, particularly in the dental setting, and to evaluate the attitudes of parents in Jordan with regard to prevention of COVID-19 transmission especially to children attending dental clinics. Methods: A cross-sectional study was carried out among parents of pediatric dental patients in Jordan. A questionnaire composed of 37 questions divided into three sections was used. The first covered socio-demographic characteristics of the sample, the second assessed parental knowledge; and the third evaluated the attitudes of parents towards COVID-19, particularly with regard to children visiting the dentist. An online form of the questionnaire was published on social media platforms. Parents who fulfilled the inclusion criteria were asked to complete the questionnaire and share it with acquaintances in a form of snowball sampling. Descriptive and analytical statistical analysis was performed using SPSS for Windows. Statistical significance was set at 0.05. Results: The number of questionnaires included in the study was 671. Only 44% of the study sample reported that they had accompanied a child to a dental clinic during the COVID-19 outbreak and 60.3% reported that the visit was for emergency reasons. Almost all the parents (94.5%) talked about COVID-19 with their children. Conclusions: Parents had good knowledge, positive attitude, and appropriate practices towards COVID-19.